Economic Efficiency In Higher Education Through Chatgpt Integration: Case Study Of Budi Utomo National Institute - Pujiani, Ida; Alijoyo, Franciskus Antonius (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research is motivated by the need for higher education institutions to enhance economic efficiency in the learning process through innovative technology. ChatGPT, as an artificial intelligence (AI) model, is expected to support more effective and efficient learning processes significantly. This study aims to evaluate ChatGPT integration's impact on economic efficiency at Budi Utomo National Institute. The research uses a quantitative method with a survey approach involving 150 respondents consisting of lecturers and students. Data collection was conducted through questionnaires, and the results were analyzed using simple linear regression techniques. The findings show that the integration of ChatGPT significantly improves operational cost efficiency in education, reduces administrative burdens, and accelerates access to learning resources. The discussion focuses on AI's long-term potential in enhancing teaching quality and the challenges of implementing such technology in higher education institutions. This study concludes that ChatGPT can be an effective tool for achieving economic efficiency in higher education, though proper strategies are needed to optimize its use sustainably.